Invisible sexual predators & their silent crimes: exploring media constructions of female teacher sex offenders - Parfitt, Kerewin (Department of Sociology, 2026)
The invisibility of female sex offenders (FSOs), and the trend of denialism surrounding the phenomenon, is the social issue that foregrounds this research. Sex offending continues to be regarded as male dominated and, as a result, research has focused almost exclusively on male sex offenders (MSOs). Recent literature has, however, observed that cases of FSOs are rising, globally, and being increasingly publicised in the media. Given media influences on public perceptions, policy action, and crime and penal policies, their construction of FSOs is a good starting point to understanding the ways in which a largely invisible phenomenon is made visible. This study, approached from a social constructionist framework, uses a qualitative desktop research design and conducts a thematic analysis of forty media articles, focusing on ten FSO cases, from seven countries. The findings position the media as complicit in the continued invisibility of FSOs. This complicity is evident through their conceptualisation of the offence; their denial of female agency; their focus on constructing FSOs in terms of social normality; their conception of victimisation; their contribution to the infamy of FSOs; and their acknowledgement of the dichotomy between MSOs and FSOs. The trends of trivialisation, leniency, and denial surrounding FSOs, both in the media and academic literature, need to be addressed. Thus, the overarching aim of this research is to make the ‘invisible' FSO visible. The term used for these women across existing literature is FSO. To challenge this veiling of harmful female sexual aggressors, I comment on the ways in which media constructions of FSOs align with understandings of male rapists and male paedophiles. The related observation that the labels of rapist and paedophile are seldom used for FSOs lays the groundwork for my argument towards the degendering of sex offender typologies. As it stands, FSOs are best conceptualised as invisible sexual predators committing silent crimes.